Levonadifloxacin, a Novel Broad-Spectrum Anti-MRSA Benzoquinolizine Quinolone Agent: Review of Current Evidence - Bhagwat SS; Nandanwar M; Kansagara A; Patel A; Takalkar S; Chavan R; Periasamy H; Yeole R; Deshpande PK; Bhavsar S; Bhatia A; Ahdal J; et al. (Dove Medical Press, 2019)
Sachin S Bhagwat,1 Manohar Nandanwar,2 Atul Kansagara,2 Anusuya Patel,3 Swapna Takalkar,1 Rajesh Chavan,4 Hariharan Periasamy,1 Ravindra Yeole,5 Prasad K Deshpande,6 Satish Bhavsar,6 Ashima Bhatia,7 Jaishid Ahdal,8 Rishi Jain,8 Mahesh Patel9 1Department of Microbiology, Wockhardt Research Centre, Aurangabad, India; 2Department of Toxicology, Wockhardt Research Centre, Aurangabad, India; 3Department of Safety Pharmacology, Wockhardt Research Centre, Aurangabad, India; 4Department of Drug Metabolism and Pharmacokinetics, Wockhardt Research Centre, Aurangabad, India; 5Department of Analytical Chemistry, Wockhardt Research Centre, Aurangabad, India; 6Department of Medicinal Chemistry, Wockhardt Research Centre, Aurangabad, India; 7Global Clinical Operations, Wockhardt Ltd, Mumbai, India; 8Department of Medical Affairs, Wockhardt Ltd, Mumbai, India; 9Drug Discovery Research, Wockhardt Research Centre, Aurangabad, IndiaCorrespondence: Sachin S BhagwatWockhardt Research Centre, Aurangabad 431006, IndiaTel +91240-669-4185Email sbhagwat@wockhardt.comAbstract: Levonadifloxacin and its prodrug alalevonadifloxacin are novel broad-spectrum anti-MRSA agents belonging to the benzoquinolizine subclass of quinolone, formulated for intravenous and oral administration, respectively. Various in vitro and in vivo studies have established their antimicrobial spectrum against clinically significant Gram-positive, Gram-negative, atypical, and anaerobic pathogens. The potent activity of levonadifloxacin against MRSA, quinolone-resistant Staphylococcus aureus, and hetero-vancomycin-intermediate strains is an outcome of its well-differentiated mechanism of action involving preferential targeting to DNA gyrase. Potent anti-staphylococcal activity of levonadifloxacin was also observed in clinically relevant experimental conditions such as acidic pH, the intracellular environment, and biofilms, suggesting that the drug is bestowed with enabling features for the treatment of difficult-to-treat MRSA infections. Levonadifloxacin also retains clinically relevant activity against resistant respiratory pathogens such as macrolide- and penicillin-resistant Streptococcus pneumoniae, Streptococcus pyogenes, Haemophilus influenzae, and Moraxella catarrhalis and, in conjunction with clinically established best-in-class human epithelial lung fluid concentration, has promising potential in the management of recalcitrant respiratory infections. Attractive features, such as resistance to NorA efflux, divergent mechanism of action in S. aureus, cidality against high-inoculum cultures, and low mutant prevention concentration, are likely to confer favorable resistance-suppression features to both agents. In vivo studies have shown promising efficacy in models of acute bacterial skin and skin structure infection, respiratory infections, pyelonephritis, and peritonitis at human-equivalent mouse doses. Both formulations were well tolerated in multiple phase I studies and overall showed a dose-dependent exposure. In particular, oral alalevonadifloxacin showed excellent bioavailability (∼90%), almost mirroring the pharmacokinetic profile of intravenous levonadifloxacin, indicating the prodrug’s seamless absorption and efficient cleavage to release the active parent drug. Hepatic impairment studies showed that clinical doses of levonadifloxacin/alalevonadifloxacin are not required to be adjusted for various degrees of hepatic impairment. With the successful completion of phase II and phase III studies for both levonadifloxacin and alalevonadifloxacin, they represent clinically attractive therapeutic options for the treatment of infections caused by multi-drug-resistant Gram-positive organisms. Herein, we review the current evidence on therapeutically appealing attributes of levonadifloxacin and alalevonadifloxacin, which are based on a range of non-clinical in vitro and in vivo investigations and clinical studies.Keywords: levonadifloxacin, WCK 771, alalevonadifloxacin, WCK 2349, broad-spectrum antibiotic, MRSA